C-reactive protein levels in acute pancreatitis and its clinical significance - Deherkar, Juthika Abhijit; Pandey, Ayush; Deshmukh, Shahaji (International Surgery Journal, 2019)
Background: Acute pancreatitis is one of the most common problems faced by surgeon in their practice. Alcohol being one of the most important etiology in country like India. The most common line of management has always been conservative until and unless surgery is indicated for its complications. Till date amylase and lipase have been used as diagnostic tool for it however certain prognostic tools like CRP are still under evaluation. Thus we have made an attempt to evaluate its significance as a prognostic tool in this study. Methods: A hospital based observational comparative prospective study was done with 100 patients to measure C-reactive protein (CRP) levels in patients of acute pancreatitis and evaluate if CRP levels predict the severity of pancreatitis. Results: The mean serum CRP level of patients with Ranson’s score <3 was significantly higher as compared to mean serum CRP level of patients with Ranson’s score ≥3 (10.54±5.00 mg/l vs 7.29±3.94 mg/l). There was significant association of serum CRP and Ranson’s score of patients. Conclusions: The rapid response of CRP to changes in the intensity of the inflammatory stimulus suggests that it might be valuable in the assessment and monitoring of acute pancreatitis. It was observed in our study that measurement of CRP level is a simple method to assess the severity of disease.